1993
DOI: 10.1111/j.1532-849x.1993.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Stress Analysis of Tooth‐to‐Implant Fixed Partial Denture Designs

Abstract: Based on the similarities in both the patterns of stress contours and the stress values generated in the two models, advocating a nonrigid connection because of a biomechanical advantage may be erroneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…Especially, the load on the implants show rise with the increase of pontic number. is is the proof of supportation of the prosthesis by the implants [12,24]. Short-term clinical success in tooth-implant-supported and implant-supported prosthesis is similar.…”
Section: Bone Lossmentioning
confidence: 90%
See 3 more Smart Citations
“…Especially, the load on the implants show rise with the increase of pontic number. is is the proof of supportation of the prosthesis by the implants [12,24]. Short-term clinical success in tooth-implant-supported and implant-supported prosthesis is similar.…”
Section: Bone Lossmentioning
confidence: 90%
“…Splinting of teeth will decrease the complication which may occur in long term, if contacts in posterior region are not hindered with prosthesis or skeletally in lateral movements. In addition, connection of natural teeth abutments decreases the incoming load on each support by dissipation [12,13]. Increase in number of teeth which are connected decreases the movement of prosthesis.…”
Section: Principles Of Implant and Natural Teeth Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no clear consensus regarding the effectiveness of this type of connectors because of the potential clinical hazard of natural tooth intrusion 5 . Several studies reported no significant difference between rigid and non-rigid connector types 12,18 .…”
Section: Introductionmentioning
confidence: 99%